Inositol polyphosphate multikinase IPMK-1 regulates development through IP3/calcium signaling in Caenorhabditis elegans. (January 2021) - Yang, Zhong-Lin; Chen, Jian-Ning; Lu, Yu-Yang; Lu, Min; Wan, Qin-Li; Wu, Gui-Sheng; Luo, Huai-Rong
Graphical abstract: Highlights: IPMK-1 is the major IP3K in C. elegans . IPMK-1 kinase activity is required for defecation rhythmic behavior and development. The mutant IPP-5 could rescue the phenotypes of IPMK-1 mutant. IPMK-1 regulates IP3/Ca 2+ homeostasis. IPMK-1 regulates defecation rhythmic behavior and development through IP3/Ca 2+ signaling. Abstract: Inositol polyphosphate multikinase (IPMK) is a conserved protein that initiates the production of inositol phosphate intracellular messengers and is critical for regulating a variety of cellular processes. Here, we report that the C. elegans IPMK-1, which is homologous to the mammalian inositol polyphosphate multikinase, plays a crucial role in regulating rhythmic behavior and development. The deletion mutant ipmk-1(tm2687) displays a long defecation cycle period and retarded postembryonic growth. The expression of functional ipmk-1 ::GFP was detected in the pharyngeal muscles, amphid sheath cells, the intestine, excretory (canal) cells, proximal gonad, and spermatheca. The expression of IPMK-1 in the intestine was sufficient for the wild-type phenotype. The IP3-kinase activity of IPMK-1 is required for defecation rhythms and postembryonic development. The defective phenotypes of ipmk-1(tm2687) could be rescued by a loss-of-function mutation in type I inositol 5-phosphatase homolog (IPP-5) and improved by a supplemental Ca 2+ in the medium. Our work demonstrates that IPMK-1 and the signaling molecule inositol triphosphate (IP3) pathway modulate rhythmic behaviors and development by dynamically regulating the concentration of intracellular Ca 2+ in C. elegans . Advances in understanding the molecular regulation of Ca 2+ homeostasis and regulation of organism development may lead to therapeutic strategies that modulate Ca 2+ signaling to enhance function and counteract disease processes. Unraveling the physiological role of IPMK and the underlying functional mechanism in C. elegans would contribute to understanding the role of IPMK in other species, especially in mammals, and benefit further research on the involvement of IPMK in disease.